Mapping high-angle basement faults in the middle benue trough, nigeria from gravity inversion surface (2009)
High-angle faults appear as vertical off-sets on a topographic surface including that derived through the inversion of gravity data. In this study of the middle Benue trough, Nigeria, gravity data for the area was bandpass filtered and inverted to generate a topographic surface map of the basement. Furthermore, a topographic slope surface map was produced by calculating the horizontal gradient magnitude over the surface. An automatic method was used to scan the horizontal gradient magnitude grid to identify maxima whose loci were mapped as high-angle faults in the basement.Three major NE-SW trending faults of regional dimension were identified. There are also shorter but significant NW-SE trendingfaults. The NE-SW and NW-SE sets are interpreted as conjugate pairs within the fracture system of the Nigerian Basement Complex.In places, segments of these faults represent bounding faults enclosing the four major sub-basins which were identifiedaround Bashar, Mutum Biyu, Wukari and Lafia.